Xrn1 Exoribonuclease-An Intrinsic Marker of Yeast Population Growth - Grousl, Tomas; Vomastek, Tomas (Frontiers in bioscience (Elite edition), 2024)
BACKGROUND: Xrn1 exoribonuclease is the major mRNA degradation enzyme in Saccharomyces cerevisiae. In exponentially growing cells, Xrn1 is localised in the yeast cells and directs the degradation of mRNA molecules. Xrn1 is gradually deposited and presumably inactivated in the processing bodies (P-bodies) as the yeast population ages. Xrn1 can also localise to the membrane compartment of the arginine permease Can1/eisosome compartment at the yeast plasma membrane. This localisation correlates with the metabolic (diauxic) shift from glucose fermentation to respiration, although the relevance of this Xrn1 localisation remains unknown. METHODS: We monitored the growth rates and morphology of Xrn1-green fluorescent protein (GFP) cells compared to wild-type and Δxrn1 cells and observed the Xrn1-GFP localisation pattern in different media types for up to 72 hours using fluorescence microscopy. RESULTS: We present the dynamic changes in the localisation of Xrn1 as a versatile tool for monitoring the growth of yeast populations at the single-cell level using fluorescence microscopy. CONCLUSIONS: The dynamic changes in the localisation of Xrn1 can be a versatile tool for monitoring the growth of yeast populations at the single-cell level. Simultaneously, Xrn1 localisation outside of P-bodies in post-diauxic cells supports its storage and cytoprotective function, yet the role of P-bodies in cell metabolism has still not yet been entirely elucidated.
Keywords: populační růst; Saccharomyces cerevisiae; Population Growth; eisosomes; Xrn1; RNA, Messenger; P-bodies; messenger RNA; Exoribonucleases; diauxic shift; yeast; exoribonukleasy